Social Demography and Living Together Practices in Kathmandu Valley of Nepal - Devkota, Narayani (Journal of Development Review, 2024)
This article gives the glimpses of socio-demographic structure and practices of ‘Living Together’ relationship in Kathmandu Valley. Conceptually, living together is a relationship between two individual living as a couple without socio-cultural and legal recognition, and they haven’t socio-cultural and legal right and responsibility too. They shared everything such as household responsibility, economic condition, sexual desire and pleasure without socio-cultural and legal recognition. Methodologically, this article is based on qualitative research paradigm, especially interpretation of narratives of informants on the practices of living together. Data was gathered through the in-depth interview with 20 informants who were in living together relationship, between 15 May to 14 June 2024 in Kathmandu valley. and respondent were selected through the snowball sampling for 16 informants and four informants from purposive sampling specially snowball sampling, because of the individual were unwilling to give recorded interview about their secret life. Research found that there was diversity in terms of caste/ethnicity, age, education, and so on. In terms of age, respondent found that 20 years to 55 years’ age group; research based on four months long to 16 years long living together relation. The level of education also found diverse from class 3 to PHD level. On the basis of gender, researcher was able to reach with 14 females, four males and two trans gender. Research was conducted in Kathmandu valley, but all respondents except one are not the permanent resident of Kathmandu valley, they belong from 10 different district. In the case of occupation forty individual (my respondent and their partner) belong 17 different occupational backgrounds, from sex worker to university professor too. More than a half of my respondent and half of my respondent’s partner were already marriage and most of them have children from first marriage, before their living together relationship. Finding of research indicate that weakening the community and religious control over the women sexuality, the age of love, affair and start a new relationshipis not restricted on young age, living together relationship is not only a choice of highly educated individual. In the case of sexuality living together relationship is choice and privilege for heterosexual couple and compulsion for homo sexual individual. This research is based on Kathmandu valley, but the living together relationship found migrant people from outside the valley, there is not specific occupational background for living together relation, and in the case of marriage living together relationship is compatibility check for some couple and new form of family formation for many people. In this way research does not found that any specific caste, age, religion, level of education, place, occupation and romanticism that play a central role in living together relationship.